Carbon black: Production, properties, and utilization - Mohamad Agus Ramly; Muji Setiyo (Mechanical Engineering for Society and Industry, 2023)
As of today, only a few people know about carbon black. Their knowledge and understanding are also limited to the fact that carbon is charcoal from coconut shells or black activated carbon. In addition, some people only know carbon as carbon copy and ink material. On the other hand, there is another type of carbon that comes from oil content and can be used for various industrial purposes. This carbon is produced and used with advanced and modern technology, which is called carbon black. Currently, by looking at the market signal, carbon black has become a very profitable commodity. Carbon black industries develop systems and technologies to produce the best quality with minimized environmental effects. In fact, because of the promising price and high market demand, carbon black factories invest in advanced production equipment. In its development, through continuous research and by utilizing advances in industrial technology, currently, carbon black can be added to various materials to improve the physical, electrical, or optical properties of the material.